A genetic variant in the catechol-O-methyl transferase (COMT) gene is related to age-dependent differences in the therapeutic effect of calcium-channel blockers. Issue 30 (July 2017) - Xu, Jiayue; Boström, Adrian E.; Saeed, Mohamed; Dubey, Raghvendra K.; Waeber, Gérard; Vollenweider, Peter; Marques-Vidal, Pedro; Mwinyi, Jessica; Schiöth, Helgi B.
Abstract : Abstract: Hypertension is the leading risk factor for cardiovascular disease and one of the major health concerns worldwide. Genetic factors impact both the risk for hypertension and the therapeutic effect of antihypertensive drugs. Sex- and age-specific variances in the prevalence of hypertension are partly induced by estrogen. We investigated 6 single nucleotide polymorphisms in genes encoding enzymes involved in estrogen metabolism in relation to sex- and age-specific differences in the systolic and diastolic blood pressure (SBP and DBP) outcome under the treatment of diuretics, calcium-channel blockers (CCBs), angiotensin-converting-enzyme inhibitors, and angiotensin-receptor blockers (ARBs). We included 5064 subjects (age: 40–82) from the population-based CoLaus cohort. Participants were genotyped for the catechol-O-methyltransferase gene ( COMT ) variants rs4680, rs737865, and rs165599; the uridine-diphospho-glucuronosyltransferase 1A gene family ( UGT1A ) variants rs2070959 and rs887829; and the aromatase gene ( CYP19A1 ) variant rs10046. Binomial and linear regression analyses were performed correcting for age, sex, body mass index, smoking, diabetes, and antihypertensive therapy to test whether the variants in focus are significantly associated with BP. All investigated COMT variants were strongly associated with the effect of diuretics, CCBs, and ARBs on SBP or DBP ( P  < .05), showing an additive effect when occurring in combination. After Bonferroni correction the polymorphism rs4680 (Val 158 Met) in COMT was significantly associated with lower SBP in participants treated with CCBs ( P  = .009) with an especially strong impact in elderly individuals (age ≥ 70) alone (Δ = −14.08 mm Hg, P  = .0005). These results underline the important role of estrogens and catecholamines in hypertension and the importance of genotype dependent, age-related adjustments of calcium-channel blocker treatment.